Coccinellidae (Coleoptera: Coccinelloidea) from Colombia: A systematic and illustrated list - González, Guillermo; Kondo, Takumasa; Gasca-Álvarez, Héctor Jaime; Sandoval-Espinel, Madelyn Katherine; Niño-Suárez, Mayra Alejandra; Moreno, Maira Alejandra Zambrano (Zootaxa, 2024)
A synopsis of the family Coccinellidae of Colombia is presented, including an annotated list of the species recorded in the country based on published data, a revision of national and foreign collections, and information obtained from citizen science. The list includes 404 species grouped in 81 genera, 21 tribes and two subfamilies. There are 395 native species recorded (among them 201 considered endemic), and nine introduced. For each species, taxonomic information, background on its biology, its usage in biological control and geographic distribution are included. Images of their habitus, living specimens and distribution maps for Colombia and the Americas are also included. Twenty species were recorded for the first time for Colombia, nine for Ecuador, five for Peru and Venezuela, three for French Guiana, two for Brazil and one for Argentina, Cuba, Paraguay, and Puerto Rico, respectively. The coccinellid fauna of Colombia is compared with other countries in South America in terms of the diversity, endemism, and geographical distribution. Two nomenclatural changes are proposed because of homonymy: Hyperaspis amati González is a new name for Hyperaspis mimica Gordon & González, 2011, and Hyperaspis octomaculata González is a new name for Hyperaspis octonotata Gordon & Canepari, 2008.